Anode modified by BiFeO3 and application in resourceful treatment of salty organic wastewater. (29th May 2019) - Zhang, Xiang; Song, Xiaoli; Lu, Zeqiang; Chen, Aiping; Li, Chunzhong
Abstract : The Ni foil or fluorine‐doped SnO2 transparent conductive glass substrates modified by BiFeO3 film with a different atomic ratio of Bi to Fe were prepared by the method of spin coating‐calcination at a different temperature. Coupling photo‐catalysis with electro‐catalysis, resourceful treatment of salty organic wastewater containing methyl orange and cadmium ion was proposed and experimentally achieved. Under visible light irradiation, the highest H2 ‐production rate (5.46 ml/h cm 2 ), degradation efficiency of methyl orange (51.6%), and the recovery precipitation weight of cadmium hydroxide (0.1846 g) were obtained with Ni foil modified by BiFeO3 (Bi:Fe = 1.10:1.00) film at 550°C of calcination. X‐ray diffraction, ultraviolet–visible diffuse reflectance spectroscopy, scanning electron microscopy, and the resourceful treatment test of salty organic wastewater were used to characterise the catalyst film.